Paediatric cardiologyHybrid stent implantation to the pulmonary artery from peripheral access via recruited systemic-pulmonary shunt - Haponiuk, Ireneusz; Chojnicki, Maciej; Steffens, Mariusz; Jaworski, Radosław; Paczkowski, Konrad; Szofer-Sendrowska, Aneta; Gierat-Haponiuk, Katarzyna (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
The implantation of vascular stents in patients with low body weight and difficult anatomy of the stenosis needs individual cannulation strategy or a hybrid approach. We present a successful balloon angioplasty with direct stent implantation to severe ostial stenosis of the left pulmonary artery to xenograft anastomosis (LPA) in a 6-year-old boy late after surgical correction of pulmonary atresia with ventricular septal defect. Peripheral approach to LPA was possible after surgical rethoracotomy and the recruitment of a left Blalock-Taussig (BT) shunt stump. The cooperation of cardiovascular intervention with surgical approach appears a safe strategy for borderline patients referred for staged treatment of complex congenital heart defects.